PENINGKATAN MINAT BELAJAR IPS PADA SISWA KELAS VII DI SMP NEGERI 13 JEMBER MELALUI MEDIA PEMBELAJARAN BERBASIS DIGITALISASI BENDA-BENDA PRASEJARAH DI KABUPATEN JEMBER - Ade Imelda Suyono; Rina Rohmawati; Moh. Il Badri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the increase in interest learning social studies using learning media based on the digitization of prehistoric objects in Jember district among class VII students at SMP Negeri 13 Jember. This type of research is classroom action research (PTK). The research subjects were 36 class VII students at SMP Negeri 13 Jember. PTK design uses Kemmis and Taggart which includes planning, action and observation, as well as reflection. The data collection technique is in the form of a test. The data analysis technique uses quantitative descriptive analysis. The results of the research show that the use of learning media based on the digitization of prehistoric objects can increase interest in studying social studies in class VII students at SMP Negeri 13 Jember. Increased interest in learning was shown by the percentage of completeness in pre-action 27.72%, in cycle I 69.44%, and in cycle II 88.89%.